2013
DOI: 10.1128/cvi.00140-13
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Secreted Antigens from Mycoplasma hyopneumoniae Delivered as a Cocktail Vaccine Enhance the Immune Response of Mice

Abstract: bMycoplasma hyopneumoniae is the etiological agent of porcine enzootic pneumonia (EP), which is a respiratory disease responsible for huge economic losses in the pig industry worldwide. The commercially available vaccines provide only partial protection and are expensive. Thus, the development of alternatives for the prophylaxis of EP is critical for improving pig health. The use of multiple antigens in the same immunization may represent a promising alternative. In the present study, seven secreted proteins o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Virginio et al [23] demonstrated that mnuA induced a strong humoral immune response when IgG was tested in the murine model; it was shown to be a strong immunogenic antigen as it significantly stimulated high levels of interferon-gamma and increased the amount of interleukin-10. When evaluating the antigenicity of proteins secreted by M. hyopneumoniae, mhp418 was recognized in serum from swine that were naturally infected by the agent [24]. The obtained results, with the presence of isolates from the same batch of animals belonging to four different genetic groups, demonstrated the possible genetic diversity of M. hyopneumoniae strains within the same batch, farm, city, and region, as has been also observed in other genetic diversity studies [20,25].…”
Section: Discussionsupporting
confidence: 74%
“…Virginio et al [23] demonstrated that mnuA induced a strong humoral immune response when IgG was tested in the murine model; it was shown to be a strong immunogenic antigen as it significantly stimulated high levels of interferon-gamma and increased the amount of interleukin-10. When evaluating the antigenicity of proteins secreted by M. hyopneumoniae, mhp418 was recognized in serum from swine that were naturally infected by the agent [24]. The obtained results, with the presence of isolates from the same batch of animals belonging to four different genetic groups, demonstrated the possible genetic diversity of M. hyopneumoniae strains within the same batch, farm, city, and region, as has been also observed in other genetic diversity studies [20,25].…”
Section: Discussionsupporting
confidence: 74%
“…Vaccine studies concerning leishmaniasis call for the critical evaluation of the parasitological and immunological parameters in murine models [ 13 , 28 ]. To properly evaluate new antigens, it is important to optimize their dose and route of administration [ 39 ]. The present study aimed to evaluate a polyproteins vaccine composed by three different antigens, based on their potential to induce a more effective protective immunity against murine VL.…”
Section: Discussionmentioning
confidence: 99%
“…The mhp0418 gene encodes a hypothetical protein expressed during Mhp infection [24], however, mhp0418 was found at low frequency in this study. When we compared the detection frequency of mhp0418 in samples from both regions studied, the gene was significantly more frequently found in the AP samples (p < 0.05) (Table 2).…”
Section: Discussionmentioning
confidence: 62%
“…The mhp0272 gene encodes a P97 paralog located on the Mhp surface [24]. Our results demonstrated that mhp0272 had a significantly higher frequency ( p < 0.05) in the ZM samples, compared to the AP samples.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation